Suicide Attempts in Turkish University Students: The Role of Cognitive Style, Hopelessness, Cognitive Reactivity, Rumination, Self-esteem, and Personality Traits - YILDIZ, MESUT (SPRINGER, 2020)
Suicide is one of the major public health problems in young adults. Detecting the risk factors and correlates among university students might help identify students who are under risk and who need early interventions for suicide prevention. The current study aimed to investigate the cognitive style, self-esteem, hopelessness, rumination, cognitive reactivity, and personality characteristics of Turkish university students, who previously attempted suicide and who did not. A total of 355 university students (34 previous suicide attempters) were recruited for this study, and they completed the Ten-Item Personality Inventory (TIPI), the Ruminative Response Scale (RRS), the Leiden Index of Depression Sensitivity-Revised, the Beck Hopelessness Scale (BHS), the Cognitive Style Questionnaire-Short Form (CSQ), the Rosenberg Self-Esteem Scale (RSES), and the Hospital Anxiety and Depression Scale. Higher RRS, BHS, CSQ scores and lower TIPI-A and RSES scores were significantly associated with a previous suicide attempt. Negative cognitive style, hopelessness, and rumination were significant correlates of a previous suicide attempt. These cognitive factors may be targets in psychotherapy to reduce suicide attempts in college-age individuals.
Keywords: Cognitive style; Hopelessness; Rumination; Suicide attempt; University students; NEGATIVE LIFE EVENTS; COLLEGE-STUDENTS; ATTRIBUTIONAL STYLE; RISK-FACTORS; DEPRESSIVE SYMPTOMS; MENTAL-DISORDERS; BIPOLAR-DISORDER; IDEATION; BEHAVIORS; THOUGHTS